China's Development Priorities - Yusuf, Shahid; Nabeshima, Kaoru (Washington, DC: World Bank, 2012)
Over the past two decades China's growth has been rapid, social indicators have improved, and poverty levels have inched downward. However, widening inequality, increasing resource and financial imbalances, and growing environmental concerns provide China with daunting challenges in improving the quality of growth. The rapid growth that will remain China's principal vehicle for raising standards of living and reducing poverty will derive from urbanization, increased market efficiency, and improvement in the technological capability of Chinese firms. But although growth will be critically important, balance among income groups and sectors is likely to be vital for social stability. The needed measures to enhance the quantity and quality of social services and a more effective safety net for the poor will require a number of institutional changes, including a reform of intergovernmental fiscal relations. This report highlights the significance of the challenges facing China and suggests policies for achieving rapid, balanced, and sustainable growth.